The Arrangement of Indonesian Religious Harmony: Lessons from Cilegon Banten - Kandung Sapto Nugroho; Rahayu Rahayu; Muhammad Adnan; Hardi Warsono (Universitas Sultan Ageng Tirtayasa, 2022)
Religion is not only worth the rights, but also the value of the obligations. Violence in the name of religion can never be justified. Secular, symbiotic, or integrated are the choices of state-religion relations. Indonesia is not a secular country, nor is it a religious state, Indonesia is not religious. Religion is the government's business. This article focuses on the lack of worship facilities in Cilegon city other than mosques. This study aims to identify, analyze religious harmony governance in Cilegon city, Banten Province. The methods used are qualitative and descriptive, with in-depth interviews, observations, document studies, and website searches accompanied by triangulation of sources and techniques. The findings do not have the operationalization of regulations and middle ground practices of religious tolerance in Cilegon. The conclusion of governance practices has not been in accordance with the principles of good governance. For example, the establishment is not a negotiable synagogue, so that the toleration practices in de jure state there isn't a worship area, and furthermore, de facto states there is a worship area.